2002
DOI: 10.1017/s1041610202008517
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Disorder: Similarities and Differences Between Patients With Illness Onset Before and After 65 Years of Age

Abstract: Background: Recent reports have suggested that bipolar disorder beginning in late life is strongly associated with organic brain disease whereas early-onset cases are more likely to be associated with a family history of mood disorder. It is not yet clear whether late-onset bipolar disorder is therefore a “phenocopy” of the classic early-onset disorder, sharing symptoms but having a different etiology, or whether people with early- and late-onset bipolar disorder have a common underlying vulnerability that int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
67
3
12

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(92 citation statements)
references
References 9 publications
10
67
3
12
Order By: Relevance
“…We have recently evaluated the age at onset for the entire population of patients with BD in contact with the Western Australian health services between 1980 and 1998. 4 We found no evidence for a bimodal distribution of the age at onset of illness in this population, as had been previously suggested by Broadhead and Jacoby 5 ( Figure). Of course, this finding could be potentially explained by the fact that these patients might have been correctly diagnosed as suffering from an organic mental disorder rather than BD.…”
Section: Comments Comments Comments Comments Commentssupporting
confidence: 76%
See 2 more Smart Citations
“…We have recently evaluated the age at onset for the entire population of patients with BD in contact with the Western Australian health services between 1980 and 1998. 4 We found no evidence for a bimodal distribution of the age at onset of illness in this population, as had been previously suggested by Broadhead and Jacoby 5 ( Figure). Of course, this finding could be potentially explained by the fact that these patients might have been correctly diagnosed as suffering from an organic mental disorder rather than BD.…”
Section: Comments Comments Comments Comments Commentssupporting
confidence: 76%
“…The onset of symptoms is usually placed between the ages of 18 and 22 years, [1][2] although a substantial proportion of patients develop the condition later in life. 3 Almeida and Fenner, 4 for example, found that 492/6182 patients with BD had illness onset at or after the age of 65 years (8% of the total sample), confirming that mania may arise for the first-ever time amongst older adults. Broadhead and Jacoby 5 observed that the distribution of age at onset amongst 35 hospitalised older adults with BD living in London was bimodal, with an early and late onset peak, which reinforced the speculation that BD with late onset may be more strongly associated with 'organic factors' than in early onset cases.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Concernant la dépression avec caractéristiques psychotiques, en population générale là encore, c'est dans la tranche d'âge des 65 ans et plus que le taux de prévalence est le plus élevé [13]. Pour le trouble bipolaire, même si la moitié des cas sont diagnostiqués avant l'âge de 35 ans, 15 à 20 % le sont après 55 ans [14].…”
Section: Prévalence De La Dépression Chez Le Sujet âGéunclassified
“…This burden is particularly high among older adults, as older patients with bipolar disorder have a higher mortality rate and use more mental health services than younger patients [3,4]. As the general population continues to age and the awareness of this disorder among older adults continues to increase [5], the costs of late-life bipolar disorder are likely to grow in the future.…”
Section: Introductionmentioning
confidence: 99%